TARI SANDAR SEBAGAI MEDIA NAUR SESANGI DI DESA ADAT SESEH, KECAMATAN MENGWI, KABUPATEN BADUNG - I Made Sugiarta -; Ni Luh Putu Wiwin Astari -; I Kadek Sumadiyasa -; Ni Kadek Elis Sukmarini - (WIDYANATYA, 2023)
ABSTRACT Hindu religious life in Bali cannot be separated from sincere moral and material offerings which we call Yadnya. Hindus in Bali also emphasize the form of offerings or Yadnya as a medium for the realization of sradha and bhakti, therefore the existing culture and traditions can be applied to support the yadnya itself. Regarding Yadnya, art always appears as part of the ceremony. Like in the Seseh Traditional Village which has the Sandar dance as a medium for Naur Sesangi. Based on this, the problems raised in this case are: (1) What is the function of the Sandar Dance as a Naur Sesangi Media in the Seseh Traditional Village (2) What educational values are contained in the Sandar Dance as a Naur Sesangi Media in the Seseh Traditional Village. The research took the form of a qualitative design using observation techniques, interviews, documentation studies and dissection with Religious theory and Value theory. Based on this analysis, the following research results were obtained: (1) The function of the Sandar Dance as a medium for Naur Sesangi in the Seseh Traditional Village, namely, (a) Religious Function, (b) Social Function, (c) Function to Repel Evil, (2) Value contained in the Sandar Dance as a medium for Naur Sesangi in the Seseh Traditional Village, namely, (a) Tattwa Educational Values, (b) Ethical Educational Values, (c) Hindu Sociocultural Educational Values, (d) Aesthetic Values. Keywords: Sandar Dance, Naur Sesangi.